(untitled) (Journal of Oriental Studies, 2018)
In this article having taken the original copy of the epos of Korkyt as a basis, leaning on conclusions and authoritative opinion of German, Turkish, Azerbaijani, Kazakh researchers, is made the review on history of emergence of the epos of Korkyt, its place in the world’s literature, also importance of the work in understanding of history and the culture of the Turkic people, a historical image of Korkyt, the language, analysis and the translations of the work. The conclusions about an essence of the epos and its translation into other languages were made, the identity of Korkyt and its epen are also defined.